2018
DOI: 10.1080/07448481.2018.1506788
|View full text |Cite
|
Sign up to set email alerts
|

Relationship intentions, race, and gender: Student differences in condom use during hookups involving vaginal sex

Abstract: Hookups-casual sexual encounters between individuals without the expectation of an ensuing dating or romantic relationship. 1-are a continued topic of interest among college and sexual health researchers. 1-4 With estimates that 60%-80% of US college students report at least one hookup during their tenure, the potential sexual health consequences posed by hookups involving penetrative sex must be considered. 1,2,5-8 The number of sexually transmitted infections (STIs) specifically attributable to hookups is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…In this study, 65.3% reported using condoms during their last sexual activity, surpassing the ndings of the latest national INJUV survey (6), which reported a percentage of 54.0% of young people using condoms in their last sexual relationship in 2022. Regarding gender differences in condom use during the last sexual encounter, the study found that men used condoms more frequently than women, which aligns with another study conducted among Canadian students (22). The years of study also showed variations, with higher condom use in 2021 compared to 2019.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, 65.3% reported using condoms during their last sexual activity, surpassing the ndings of the latest national INJUV survey (6), which reported a percentage of 54.0% of young people using condoms in their last sexual relationship in 2022. Regarding gender differences in condom use during the last sexual encounter, the study found that men used condoms more frequently than women, which aligns with another study conducted among Canadian students (22). The years of study also showed variations, with higher condom use in 2021 compared to 2019.…”
Section: Discussionsupporting
confidence: 84%
“…It is crucial to interpret this data in conjunction with the factors associated with early sexual initiation. In Chile, for example, a study found that family factors such as not being raised by both parents, poor parent-child relationships, poor family communication, adolescent motherhood, employed mothers, and family dysfunction were associated with early sexual activity initiation (22). Speci cally, regarding sexual activity initiation before the age of 15, there were differences between men and women, with men surpassing women by 1.4 points, consistent with the age difference and ndings from global research (18, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we had more women in the promotion-focused group and more men in the prevention-focused group. Past evidence has shown that women (vs. men) have less control over condom use and are less comfortable using condoms (Farmer & Meston, 2006;Hall et al, 2019), which is congruent with having a promotion (vs. prevention) focus. We also found that women, LGBTQI+ participants, those who received higher education, and Portuguese participants reported being more knowledgeable about STIs and enacted more actions toward sexual health.…”
Section: Discussionmentioning
confidence: 99%
“…Between 30% and 60% of university students report at least one casual sex experience without condoms during their academic life [30][31][32]. The academic context is a situational influence that creates opportunities for risky behavior.…”
Section: Introductionmentioning
confidence: 99%